2008
DOI: 10.1088/1748-9326/3/4/045020
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of vertical velocity in marine stratocumulus: comparison of large eddy simulations with observations

Abstract: We simulated a marine stratus deck sampled during the Marine Stratus/Stratocumulus Experiment (MASE) with a three-dimensional large eddy simulation (LES) model at different model resolutions. Various characteristics of the vertical velocity from the model simulations were evaluated against those derived from the corresponding aircraft in situ observations, focusing on standard deviation, skewness, kurtosis, probability density function (PDF), power spectrum, and structure function. Our results show that althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…The range of σ w shown in Fig. 4 is in good agreement with in situ measurements of vertical velocity at cloud base in marine stratocumulus (Peng et al, 2005;Guo et al, 2008), and continental regions (Fountoukis et al, 2007;Tonttila et al, 2011), showing σ w mostly between 0.2 and 1 m s −1 . However, global measurements of σ w have not been reported.…”
Section: Subgrid-scale Vertical Velocitysupporting
confidence: 83%
“…The range of σ w shown in Fig. 4 is in good agreement with in situ measurements of vertical velocity at cloud base in marine stratocumulus (Peng et al, 2005;Guo et al, 2008), and continental regions (Fountoukis et al, 2007;Tonttila et al, 2011), showing σ w mostly between 0.2 and 1 m s −1 . However, global measurements of σ w have not been reported.…”
Section: Subgrid-scale Vertical Velocitysupporting
confidence: 83%
“…Moreover, it has been noted that also the vertical resolution of a model has an effect on the representation of vertical velocities. Guo et al (2008) suggested that a vertical resolution of about 10 m is needed to robustly resolve the higher order statistical moments of vertical velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring vertical velocities in the atmosphere is difficult, mostly because of their relatively small magnitude. In-situ measurements are, in practice, only possible with research aircraft (Duynkerke et al, 1999;Rodts et al, 2003;Snider et al, 2003;Guo et al, 2008;Lu et al, 2009;Ghate et al, 2010), although mast measurements can be made in layers close to the surface (up to an altitude of a few hundred meters). The aircraft measurements are usually related to intensive field campaigns with limited spatial and temporal coverage, which restricts their usability.…”
Section: Introductionmentioning
confidence: 99%
“…Marine stratocumulus updraughts are generally quite low, for example Guo et al (2008) present PDFs of vertical velocity in marine stratocumulus clouds measured during the Marine Stratus/Stratocumulus Experiment (MASE), they found that characteristic updraughts (w) were always < 0.2 m s −1 at the middle and base of the cloud, but found slightly higher updraughts close to the cloud top. Guibert et al (2003) Table 3 shows frequency statistics for the updraught (w) simulated in the UK Met Office Large-Eddy Simulation Model (LEM, 3-D) for the ASTEX GCSS Sc-Cu transition case (Bretherton et al, 1999) (A.…”
Section: In-cloud Updraught Velocitymentioning
confidence: 99%